Reducing Conflict in the Wildland-Urban Interface - Martha C. Monroe (EDIS)
Revised! FOR-198, a 3-page illustrated fact sheet by Martha C. Monroe, provides extension agents and resource managers with suggestions for strategies to approach any conflict. Includes suggested readings. Published by the UF School of Forest Resources and Conservation, July 2008.